World Socialism in the Twenty-First Century: New Structure, New Features and New Trends. Issue 2 (3rd April 2017) - Jiang, Hui
ABSTRACT: This paper discusses the reality and the prospect of the world socialist movement in the twenty-first century. Capitalist crises are regarded as important opportunities to study the characteristics of world socialist development in this paper. The development characteristics and the general patterns of world capitalism and world socialism in their mutual competition after the three capitalist crises are studied first. Then, after analysis, the author believes that there are four characteristics of world socialism: the socialist system has gained a wider institutional advantage over capitalism; China has become a mainstay of the development and revitalization of world socialism; in their long struggle, the balance of power between world socialism and world capitalism will change historically in favor of world socialism; the number of socialist countries and the degree of the socialism realization has become the standards to judge socialist development. Finally, the author concludes that the possibility of the new development of world socialism will rely on the organic unifications between its nationalism and internationalism, its regionalism and cosmopolitanism, working class movement and mass movement, as well as social development and ecological civilization.